IMPLEMENTATION OF GOOGLE CLASSROOM TO IMPROVE ONLINE LEARNING ACTIVITY FOR STUDENTS OF SMK NEGERI 1 PATUMBAK - Amra, Yetty (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2021)
Google Classroom (Google Classroom) is an online learning application that can be used for free. Teachers can create their own class and share the class code or invite students. This Google Classroom is intended to assist the process of learning activities such as finding or overcoming learning difficulties, sharing lessons and making assignments without having to attend class. Education providers in the vocational field cannot be separated from advances in technology and information. Advances in technology and information that can have positive and negative impacts need to be responded to carefully and appropriately. The use of advances in technology and information in vocational learning can make a positive contribution to the achievement of learning objectives, both for students and for teachers themselves. The purpose of research in this activity is to find out whether the facilities and infrastructure of online learning activities (online) have been fulfilled or not, to find out whether the application of Google Classroom is in accordance with the online learning process (online), to find out the extent to which students understand the material learning, especially the lessons of Pratikum Accounting for Service, Trade and Manufacturing Companies and to eliminate boredom and boredom that exist in students during the online learning process (online)